Knowledge and attitude of dental practitioners about probiotics in Alkharj, Kingdom of Saudi Arabia - Inderjit M Gowdar; Abdualrhman Aljuma; Naif Alenazi; Osama Alqahtani; Talal Altayyar; Abdullah Almiqren (Journal of Pharmacy and Bioallied Sciences, 2023)
Background: Probiotics are dietary supplements have found their usage mainly for gastrointestinal problems. Recently, oral health benefits of probiotics are investigated and their use for prevention of oral diseases such as dental caries, periodontal problem, and halitosis are established. Aim: The aim of the study is to assess the knowledge and attitude about probiotics among private dental practitioners in Alkharj, Saudi Arabia. Material and Methods: A cross-sectional study conducted on a total of 170 dentists practicing in alkharj. The subjects completed a questionnaire that consisted of information related to assess the awareness, knowledge, and attitude about probiotics. The collected data were expressed as number and percentages. Results: 96.47% of dentists were aware of the probiotics, while 82.3% of dentists think probiotics helps in improving health. 76.2% have used probiotics for some reason. 81.7% were of the intention to use probiotics for prevention of oral disease. Conclusion: This study revealed good awareness of probiotics among dentists in Alkharj. Lack of adequate knowledge about use of probiotics for oral health needs to be addressed.